Pengaruh Pemanfaatan Absensi Finger Print dan Motivasi Terhadap Kinerja Pegawai Dengan Disiplin Kerja Sebagai Variabel Mediasi Pada Badan Pengelola Keuangan dan Aset Daerah Pemerintah Kabupaten Banyuasin. - Sinta Shinta; Trisninawati Trisninawati (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to determine the effect of finger print attendance and motivation on employee performance directly or indirectly with work discipline as a mediating variable. This study uses a quantitative approach. This research was conducted at the Regional Financial and Asset Management Agency of the Banyuasin Regency Government which is located at Jl.A. Rachman Tamim No.14 South Sumatra Hall Base. The population used in this research was all BPKAD employees, totaling 90 people. The sampling technique uses the sample census method by using all members of the population as samples. There are two sources of data used in this research, namely primary and secondary data. The techniques used in collecting data for this research were observation, interviews and distributing questionnaires. The measurement variables in this study use a Likert scale. In this study the data analysis method used is path analysis (Path Analysis) using the Structural Equestion Model (SEM) application version 3.0. Overall, the seven hypotheses proposed in this study were accepted. The results of this study indicate that finger print absence, motivation, and work discipline have a positive and significant effect on good employee performance and work discipline plays a role in mediating the effect of finger print absence and motivation on employee performance where the value obtained is less than 0.05.